Knowledge Management As a Strategic Approach in Enhancing Customer Relationship Management : A Case Analysis of Financial Industry in Malaysia - Lim, Hong Woo (2010)
Aim of this research is to investigate the multidimensionality of knowledge management (KM) practices and its relationship with customer relationship management (CRM) metrics in Malaysian financial sector.